KEBIJAKAN STRATEGI HEDGING NORWEGIA TERHADAP PENINGKATAN AKTIVITAS MILITER RUSIA DI ARKTIK - Wandy Ardiyansyah Hasibuan; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Arctic region in the north has changed geopolitical conditions which were previously in Low Political Tension to High Political Tension as a result of climate change which causes the ice at the poles to melt. The melting of the Arctic ice has opened several economic opportunities, such as opening up access to Arctic natural resources to strategic projects such as new maritime routes. In addition, the opening of this opportunity makes the Arctic states, especially the Arctic coastal states, act more aggressively in protecting their national interests in the Arctic. Russia is one of the states that has made increasing military capabilities in the Arctic to maintain its security. The increase in Russian military activity in the Arctic makes Norway as a neighboring state feel threatened. By realizing this phenomenon, Norway uses a hedging strategy by considering its military, economic and diplomatic capabilities to deal with this threat.This research uses qualitative research methods, with data collection techniques through literature studies sourced from several books, journals, research documents, articles, websites, and other sources deemed by the author. This research also uses the Neorealism perspective and Balance of Power Theory.The results of this research show that Norway uses the type of Politico-Military Hedging where Norway tries to balance Russia's military power while strengthening diplomatic relations between the two countries. This is done by taking advantage of the geographical proximity of the countries so as to be able to create strategic bilateral relations. Keywords: Hedging, National Security, Arctic Geopolitic. Norway, Russia